2022
DOI: 10.2147/rru.s388464
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Double Stranded RNA Provokes Smooth Muscle Contractions and Structural Modifications in Bladder Ischemia

Abstract: Purpose Growing evidence suggests that ischemia provokes detrusor overactivity and degenerative responses in the bladder. Underlying mechanisms appear to involve modification of smooth muscle contractile rudiments by hypoxia, redox, cellular stress and cell survival signaling. Downstream pathways of cellular stress and stress response molecules eliciting bladder dysfunction in ischemia remain largely elusive. Our goal was to define the role of double stranded RNA (dsRNA), a stress response molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Several other studies have shown that human bladder blood flow decreases with aging in both men and women, and decreased bladder blood flow significantly correlates with reduced bladder compliance and the development of LUTS . Studies of animal models have revealed that ischemia compromises the bladder proteomic profiles and instigates a cascade of downstream signaling pathways with critical structural and functional consequences [37][38][39][40][41]. These observations, cumulatively, suggest that therapeutic strategies to improve bladder perfusion could prevent or reverse detrusor overactivity and LUTS in patients with pelvic ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several other studies have shown that human bladder blood flow decreases with aging in both men and women, and decreased bladder blood flow significantly correlates with reduced bladder compliance and the development of LUTS . Studies of animal models have revealed that ischemia compromises the bladder proteomic profiles and instigates a cascade of downstream signaling pathways with critical structural and functional consequences [37][38][39][40][41]. These observations, cumulatively, suggest that therapeutic strategies to improve bladder perfusion could prevent or reverse detrusor overactivity and LUTS in patients with pelvic ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…These observations, cumulatively, suggest that therapeutic strategies to improve bladder perfusion could prevent or reverse detrusor overactivity and LUTS in patients with pelvic ischemia. Downstream mechanisms mediating overactivity and structural damage in bladder ischemia appear to involve disruption of cellular energy homeostasis, cellular stress, and cell survival signaling [37][38][39][40][41]. It is thought that the upregulation of cellular stress response molecules by ischemia activates homeostatic mechanisms to signal nutrient deficiency, hypoxic stressors, and cell danger [42][43][44][45][46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations